Notes on Humans as Prey of Reticulated Pythons Malayopython reticulatus (Serpentes: Pythonidae) in Indonesia - Iqbal, Muhammad; Sari, Diah Komala; Arifah, Nur; Widayanti, Gusti Ayu; Aprillia, Ina (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
This study examines documented cases of humans being preyed upon or attempted to be preyed upon by Reticulated Pythons Malayopython reticulatus in Indonesia, spanning nearly a century from 1927 to 2025. Our study reveals 17 incidents, with snakes involved measuring between 5-8 meters in length. The victims' ages ranged from 13 to 90 years old, with 13 fatalities reported. Both males and females were affected, with 8 incidents involving men and 8 involving women. Sulawesi emerges as a hotspot for such encounters, accounting for a significant proportion of reported cases. This study highlights the importance of understanding human-python encounters and promoting a more harmonious coexistence between humans and wildlife in Indonesia. Keywords: human-wildlife coexistence, Indonesia, large snake, Malayopython reticulatus, Reticulated Python.